Physicochemical, microbiological and sensory characterization of liquor obtained from atemoya fruit (Annona cherimola×Annona squamosa) - Martínez Girón, Jader; Reina Hernandez, Bryan; Arias Rodas, Anlly Lorena; Hernandez Montaña, Jeniffer Carolina; Agudelo Burbano, Jorge Humberto (Scientia et Technica, 2019)
In this study the physicochemical, microbiological and sensorial characterization of the liquor obtained from atemoya fruit. The fermented beverage was made using fruit pulp (5 %), water (78 %), acidulant (citric acid 0.04 %), pH regulator (diammonium phosphate 0.04%), sugar (15%) and yeast (Saccharomyces cerevisiae 1.92 %). The process of obtaining the liquor included a stage of selection, cleaning and disinfection of the fruit, characterization of the pulp, pulping, mixing, fermentation, filtration, clarification and packaging. The obtained results evidenced a good sensory acceptance in relation to the texture, color, flavor and smell. A pH of 3.78, volatile acidity of 0.08 %, density of 1.10 g / mL, reducing sugars of 10.56 %, alcohol grade of 9.77 ° GL, percentage of 67 ppm methanol, E. coli absent, 90 CFU / mL aerobic mesophiles count, and 50 UFC / mL yeast and fungal counts. Given the above, it is concluded that the liquor obtained is a physicochemical, microbiological and sensorial stable drink, because it meets the quality requirements of Colombian Technical Standard 708 of 2000, established for fruit wines.